PENGARUH KOMPETENSI, INDEPENDENSI DAN SKEPTISME PROFESIONAL TERHADAP KUALITAS AUDIT APARAT INSPEKTORAT PEMERINTAH DI PROVINSI MALUKU - NICODEMUS RAHABEAT (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to analyze and prove empirically the effect of competence, independence, and professional skepticism simultaneously or partially on the audit quality of the regional government inspectorate apparatus. The research was conducted at the Maluku Provincial Government Inspectorate, Ambon City Government Inspectorate, Central Maluku Regency Government Inspectorate and Southeast Maluku Regency Government Inspectorate. Respondents in this study amounted to 56 auditors Data were analyzed using multiple regression analysis. The results of the study showed that professional competence and skepticism had a positive and significant effect on audit quality, while the independence variable had a positive but not significant effect on audit quality.